Depresi Menghadapi Pandemi Covid-19 pada Masyarakat Perkotaan (Studi Literatur) - Giofanny F Lempang; Wingga Walenta; Khalisa A Rahma; Nova Retalista; Fransiska J Maluegha; Firman Ichsan Putra Utomo (LPPM Universitas Trunojoyo Madura, 2021)
In the early 2020, there was an outbreak of a disease that attacks the human respiration and is caused by the coronavirus disease. The spread of this virus has an impact on world conditions, especially on the country's social and economic conditions. This is because the government is implementing a lockdown system to prevent the spread of the virus. Some activities are carried out at home because of government regulations for social distancing. However, the existence of these rules makes it difficult for some people to adapt to situations such as doing activities at home and limiting themselves from interacting so that they may be prone to experiencing anxiety which results in depression in society.